EFFECT OF SOME PRESERVATION PROCESSES ON THE PHYTOCHEMICAL COMPOUNDS WITH ANTIOXIDANT ACTIVITIES OF BROCCOLI - Walaa El-Shalakany; M Shatlah; M Atteia; Faten, B. EL-Kasas; Soher, S. Mostafa; G.A . Abd EL-Malak (Arab Universities Journal of Agricultural Sciences, 2009)
s of broccoli using steam or immersion in hot water as traditional technology and storage conditions by either canning or freezing on the content of compounds with antioxidant properties, i.e. vitamin C, carotenoids, chlorophyll, polyphenol and flavonoid compounds parameters was investigated. Results show that the content of carotenoids was 11.41µg/g while the content of chlorophyll A and chlorophyll B was 30.66 and 9.79µg/g, respectively. The content of both carotenoids and total chlorophyll were decreased after being treated prior to different period storage for 3 and 6 month. Fresh broccoli had 40.45µg/g total chlorophyll this content decreased more significantly for the control (fresh broccoli) than for treated and different storage samples. The content of vitamin C was 124.24 mg/100g. Frozen broccoli after blanching by steam and immersion in hot water at 0 times decreased the percent of ascorbic to 83.85 and 75.89%, respectively.  Jarred and canned broccoli with dill, coriander and parsley additives showed decrease in ascorbic acid to 45.98 and 40.55% meanwhile, jarred and canned broccoli without additives decreased ascorbic acid to 43.34 and 39.01%, respectively. Total polyphenols and flavonoids were 276.82 and 7.64 mg/100g on fresh weight. These contents were decreased after processing and different storage conditions. The present of antioxidant activity in fresh broccoli was 75.50%. The degradation of antioxidant activity was increased after 6 month period. The highest degradation observed with canned broccoli without additive while the lowest degradation showed with frozen broccoli blanched by steam which the percents of total antioxidant activities were14.84 and 29.65 %, respectively. The content of ferrous and zinc was 6.4 and 3.9 mg/100g on dry weight. Ferrous increased to 7.0 and 8.4 mg/100g with Jarred with dill, coriander and parsley additives and storage for 3 and 6 month broccoli and to 9.3 and 8.7 mg/100g with canned broccoli with dill, coriander and parsley additives.